Scale-up for single screw extrusion of polymeric materials - Nastaj, Andrzej (Polimery, 2021)
A method of scaling-up the single screw extrusion of polymeric materials has been developed based on the process simulation studies using the evolutionary techniques (genetic algorithms). The simulation tests were carried out using the GSEM extrusion simulation program, while the scaling-up was carried out on the basis of the GASES evolutionary scaling-up program specially developed for this purpose. Scaling-up has been performed according to the criteria of unit energy consumption, polymer melting rate and polymer temperature, obtaining a significant increase in extrusion throughput.